Malignant granular cell tumor of chest wall: a case report - Flauto, Fabiano; Servetto, Alberto; Bianco, Roberto; Formisano, Luigi (Frontiers in Oncology, 2024)
BackgroundGranular Cell Tumors (GCTs), also known as Abrikossoff tumors, are rare neoplasms that typically originate from Schwann cells. These tumors most commonly occur in the head and neck region, particularly the tongue. While GCTs are generally benign, less than 2% of cases exhibit aggressive biological features such as rapid growth, high recurrence rates, and metastasis. In this report, we present a rare case of a Malignant Granular Cell Tumor (MGCT) of the chest wall, which posed significant challenges in both characterization and management.Case PresentationA fifty-year-old man underwent an ultrasound examination for a nodular mass on his right chest wall. The ultrasound revealed a firm, hard mass measuring 2 cm x 2 cm with an uncertain diagnosis. A fine-needle aspiration biopsy (FNAB) guided by ultrasound was performed, resulting in a diagnosis of Abrikossoff tumor. The patient subsequently underwent radical excision of the mass, which confirmed the initial diagnosis. Nine months after surgery, a new mass with similar characteristics was detected during a physical examination. The patient underwent a second surgery, but this time the histopathological examination was negative for neoplastic cells. However, another mass appeared at the same site as the previous surgical excision. A CT scan and MRI of the right chest wall confirmed the presence of a 2 cm x 2 cm nodular mass. The patient then underwent a deeper excision. Histomorphological and immunohistochemical assessments confirmed the recurrence of MGCT.ConclusionThis case highlights the malignant potential of GCTs. The numerous local recurrences necessitated three surgeries and additional procedures. The aggressive nature of this pathology underscores the complexity of managing these tumors, which are poorly understood and lack proven post-operative strategies for controlling local and distant disease.